Pengaruh Uji Efek Tonikum Ekstrak Etanol Rimpang Temu Giring (Curcuma heyneana Val) Terhadap Mencit - Wiwik Rosi Wiyanti; Susi Endrawati - Poltekkes Bhakti Mulia (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2017)
Abstract: Rhizome Rally Leads have chemical constituents of flavonoids, saponins and essential oils, efficacious as a tonic. The purpose of research, determine the effect of ethanol extract of rhizome Rally Leads to a tonic effect and dose of ethanol extract of rhizome Intersection dribbles most effective. An experimental study to test the difference in the dose of ethanol extract of the rhizome Rally Leads dose of 100 mg / kg, 200 mg / kg, and 400 mg / kg. Rhizome Rally Leads macerated with ethanol 96% and then tested on mice. Analysis of the results by observing the length of time from the start of mice exhausted tired to swim, mice were given ethanol extract and fresh again. Results yield of ethanol extract of the rhizome maceration Rally Leads 9.3225% b/b. The ethanol extract of rhizomes Rally Leads (Curcuma heyneana Val) at a dose of 400 mg / kg had a tonic effect with an average of 11 minutes, a dose of 200 mg / kg with an average of 6.25 minutes, and a dose of 100 mg / kg with an average of 3.25 minutes. Conclusion: (1) The ethanol extract of rhizomes Rally Leads (Curcuma heyneana Val) at all doses showed dose variation tonic effect on mice. (2). The ethanol extract of rhizomes Rally Leads (Curcuma heyneana Val) at a dose of 400 mg / kg showed the most effective tonic effect.Keywords: Curcuma heyneana Val, tonic effect, ethanol extract, flavonoidÂ Abtrak: Rimpang Temu Giring mempunyai kandungan kimia flavonoid, saponin dan minyak atsiri, berkhasiat sebagai tonikum. Tujuan penelitian, mengetahui pengaruh ekstrak etanol rimpang Temu Giring terhadap efek tonikum dan dosis ekstrak etanol rimpang temu giring yang paling efektif. Penelitian eksperimental dengan melakukan uji perbedaan dosis ekstrak etanol rimpang Temu Giring dosis 100 mg/kg BB, 200 mg/kg BB, dan 400 mg/kg BB. Rimpang Temu Giring dimaserasi dengan pelarut etanol 96% kemudian diujikan terhadap mencit. Analisis hasil dengan cara observasi lama waktu lelah dari mulai mencit dilelahkan dengan berenang, diberi ekstrak etanol dan mencit segar kembali. Hasil rendemen maserasi ekstrak etanol rimpang Temu Giring 9,3225% Ekstrak etanol rimpang Temu Giring (Curcuma heyneana Val) pada dosis 400 mg/kg BB memiliki efek tonikum dengan rata-rata 11 menit, dosis 200 mg/kg BB dengan rata-rata 6,25 menit, dan dosis 100 mg/kg BB dengan rata-rata 3,25 menit. Kesimpulan: (1) Ekstrak etanol rimpang Temu Giring (Curcuma heyneana Val) pada dosis semua variasi dosis menunjukan efek tonikum terhadap mencit. (2). Ekstrak etanol rimpang Temu Giring (Curcuma heyneana Val) pada dosis 400 mg/kg BB menunjukan efek tonikum yang paling efektif.Katakunci: Curcuma heyneana Val, efek tonikum, ekstrak etanol, flavonoid